The Evaluation of Ideological Trends in Recent Soviet Literary Scholarship - Mondry, Henrietta (Slavistische Beitraege, 1990)
Since the publication of formerly forbidden und unpublished texts constitutes the main trend of Glasnost', this study has as ist aim the isolation of main trends in the process of the re-evaluation of the cultural heritage of the past by Soviet literary scholarship. The analysed authors will be divided into four main groups: 1. Accepted 19th century classics (e.g. Goncharov); 2. Formerly forbidden 20th century writers (e.g. Zamiatin); 3. Formerly forbidden 19th century writers (e.g. Rozanov and Leontiev); 4. Hagiographic classics of the 20th century Soviet period (e.g. Gorkij).